inggris - Duwi Aprilia; Yanuarita Sutikno, Putri (Jurnal Pendidikan dan Pengajaran, 2024)
The current problem is that mathematics is complex because it relates to formulas and arithmetic. This impacts the low mathematics abilities of elementary school students in Indonesia, so they must be improved. Based on this, this research aims to analyze the influence of song media on the mathematics learning outcomes of third-grade elementary school students. This type of research is a quasi-experimental research with a one-group pretest-posttest design. The subjects of this research were a total of 36 students. The method used to collect data is a test. The instrument used to collect data is the test question sheet. The technique used to analyze data is inferential statistical analysis. The results of the research show that the use of song media influences learning outcomes in flat-figure mathematics. The test results show that there are differences in learning outcomes between students who use song media and students who do not use song media in learning mathematics. It was concluded that song media can improve mathematics learning outcomes in third-grade students, especially in mathematics learning.